Middle Wisconsinan Climate Fluctuations Recorded in Central Alaskan Loess - Begét, Jim (Géographie physique et Quaternaire, 1990)
ABSTRACTFluctuations in Middle Wisconsinan environments are recorded in high resolution proxy climatic curves derived from magnetic susceptibility profiling of central Alaskan loess. Two intervals of low wind intensity and climatic amelioration, separated by a period of somewhat higher wind intensity, can be recognized in several loess records of the Middle Wisconsinan. Radiocarbon dates from loess in the Fox Permafrost Tunnel indicate that the culmination of the later period of low wind intensity occurred ca. 30-32.000 yr BP, and was associated with thermal degradation of permafrost. An older period of low wind intensity early in the Middle Wisconsinan, ca. 50-60,000 yr BP, is correlative with a fossil wood horizon in the permafrost tunnel and a widespread paleosol in loess sections. Warm intervals of similar age are recorded in the Grande Pile pollen record, in ice cores and in marines cores. The 30-32,000 yr BP and the 50-60,000 yr BP warm events recorded in Alaskan loess sequences may have been caused by "greenhouse" warming produced by transient increases in atmospheric CO2 as recorded in the Vostok ice core. A Middle Wisconsinan interval of higher wind intensity, associated with the development of ice wedges, may reflect climatic cooling due to low atmospheric CO2 values ca. 42,000 yr BP.